2022
DOI: 10.3389/fmicb.2022.953234
|View full text |Cite
|
Sign up to set email alerts
|

High-Altitude Drives the Convergent Evolution of Alpha Diversity and Indicator Microbiota in the Gut Microbiomes of Ungulates

Abstract: Convergent evolution is an important sector of evolutionary biology. High-altitude environments are one of the extreme environments for animals, especially in the Qinghai Tibet Plateau, driving the inquiry of whether, under broader phylogeny, high-altitude factors drive the convergent evolution of Artiodactyla and Perissodactyla gut microbiomes. Therefore, we profiled the gut microbiome of Artiodactyla and Perissodactyla at high and low altitudes using 16S rRNA gene sequencing. According to cluster analyses, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…We analyzed the gut microbiomes of 108 samples representing 16 species belonging to nine families and 14 genera to explore the convergent evolution of the gut microbiome. 16S rRNA gene data of the gut microbiome of the nine species ( Cuon alpinus [Wu et al, 2016 ], Canis lupus [Wu et al, 2017 ], Vulpes Vulpes [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], V. Corsac [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], Cervus elaphus [Wang et al, 2019 ], Ovis musimon [Sun et al, 2019 ], Pantholops hodgsonii [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], Pseudois nayaur [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], and Bos grunniens [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ]) were obtained by sequencing in our laboratory. Other 16S rRNA gene data ( C. Nippon [Guan et al, 2017 ], Moschus chrysogaster [Sun et al, 2020 ], Halichoerus grypus [Watkins et al, 2022 ], Nyctereutes procyonoides [Ishida‐Kuroki et al, 2020 ], Enhydra lutris nereis [Dudek et al, 2022 ], Balaenoptera physalus , and Physeter microcephalus [Glaeser et al, 2022 ]) were downloaded from the NCBI SRA database ( www.ncbi.nlm.nih.gov ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the gut microbiomes of 108 samples representing 16 species belonging to nine families and 14 genera to explore the convergent evolution of the gut microbiome. 16S rRNA gene data of the gut microbiome of the nine species ( Cuon alpinus [Wu et al, 2016 ], Canis lupus [Wu et al, 2017 ], Vulpes Vulpes [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], V. Corsac [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], Cervus elaphus [Wang et al, 2019 ], Ovis musimon [Sun et al, 2019 ], Pantholops hodgsonii [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], Pseudois nayaur [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ], and Bos grunniens [Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ]) were obtained by sequencing in our laboratory. Other 16S rRNA gene data ( C. Nippon [Guan et al, 2017 ], Moschus chrysogaster [Sun et al, 2020 ], Halichoerus grypus [Watkins et al, 2022 ], Nyctereutes procyonoides [Ishida‐Kuroki et al, 2020 ], Enhydra lutris nereis [Dudek et al, 2022 ], Balaenoptera physalus , and Physeter microcephalus [Glaeser et al, 2022 ]) were downloaded from the NCBI SRA database ( www.ncbi.nlm.nih.gov ).…”
Section: Methodsmentioning
confidence: 99%
“…The gut microbiome is an important factor for host adaptations to the environment (Wang et al, 2019 ; Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ). Wang, Shang, Wu, et al ( 2022 ) found that the gut microbiome function of red and corsac foxes can help hosts adapt to different environmental niches.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, at an altitude of 4,331 m, the relative abundance of Firmicutes and Bacteroidetes in pikas’ intestines significantly differs from that at 3,694 m and 3,856 m ( Obregon-Tito et al, 2015 ). Studies on wild ungulates at high altitudes (Yaks, Tibetan wild donkeys, Tibetan antelopes, and Bighorn sheep) also reveal that Firmicutes/Bacteroidetes ratios are higher than those in low-altitude ungulates, with Firmicutes and Proteobacteria being the most enriched phyla in the intestinal microbiota of high-altitude ungulates ( Table 1 ; Guo et al, 2014 ; Du et al, 2022 ; Wang et al, 2022 ). In particular, the Firmicutes/Bacteroidetes ratio (F/B ratio) in the intestinal microbiota of high-altitude mammals such as Plateau pikas, Tibetan macaques, Tibetan antelopes, Mouflons, and Blue sheep exceeds that of low-altitude mammals.…”
Section: The Changes In Intestinal Microbiota After Exposure To High-...mentioning
confidence: 99%
“…In recent years, there has been increasing recognition of the significant impact of environmental factors on the intestinal microbiota ( Ma et al, 2019 ; Wang et al, 2022 ). Specifically, research has highlighted the role of the high-altitude hypoxic environment in shaping the composition and structure of the intestinal microbial community ( Bai et al, 2022 ; Wang et al, 2022 ). However, our understanding of the precise effects of extreme environments, such as high altitudes, on the intestinal microbiota remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…The high altitude rumen microbiota of yak and Tibetan sheep exhibited a convergent phenomenon, with significantly lower levels in production of methane and volatile fatty acids (VFAs) (Zhang et al, 2016). The high altitude environments drive the diversity of gut microbiota composition and convergent evolution of indicator microbiota in ungulates (Wang et al, 2022). Studies on a variety of ungulates living in high altitude environments, such as the Tibetan antelope (Pantholops hodgsoni) and Tibetan sheep, also found that they have a similar composition of gut microbiota (Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%